2000
DOI: 10.1128/mcb.20.13.4948-4957.2000
|View full text |Cite
|
Sign up to set email alerts
|

Ribosomal DNA Replication Fork Barrier and HOT1 Recombination Hot Spot: Shared Sequences but Independent Activities

Abstract: In the ribosomal DNA of Saccharomyces cerevisiae, sequences in the nontranscribed spacer 3 of the 35S ribosomal RNA gene are important to the polar arrest of replication forks at a site called the replication fork barrier (RFB) and also to the cis-acting, mitotic hyperrecombination site called HOT1. We have found that the RFB and HOT1 activity share some but not all of their essential sequences. Many of the mutations that reduce HOT1 recombination also decrease or eliminate fork arrest at one of two closely sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
83
1

Year Published

2001
2001
2009
2009

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(86 citation statements)
references
References 45 publications
2
83
1
Order By: Relevance
“…Interestingly, recombination rates are significantly lower than would be expected for such a large and repetitive locus, suggesting that recombination is somehow suppressed (Petes 1980). Furthermore, recombination levels are reduced despite the presence of several sequence elements within rDNA that can stimulate recombination (Keil and Roeder 1984;Voelkel-Meiman et al 1987;Brewer and Fangman 1988;Kobayashi et al 1992Huang and Keil 1995;Gruber et al 2000;Ward et al 2000). These findings suggest that both positive and negative regulatory mechanisms have evolved to properly control recombination levels of rDNA.…”
mentioning
confidence: 76%
“…Interestingly, recombination rates are significantly lower than would be expected for such a large and repetitive locus, suggesting that recombination is somehow suppressed (Petes 1980). Furthermore, recombination levels are reduced despite the presence of several sequence elements within rDNA that can stimulate recombination (Keil and Roeder 1984;Voelkel-Meiman et al 1987;Brewer and Fangman 1988;Kobayashi et al 1992Huang and Keil 1995;Gruber et al 2000;Ward et al 2000). These findings suggest that both positive and negative regulatory mechanisms have evolved to properly control recombination levels of rDNA.…”
mentioning
confidence: 76%
“…As for cis elements required for RFB activities, the work by Ward and coworkers (38) showed that some DNA elements are shared with those required for HOT1 activity, but others are required for one activity but not for the other. Although RFB activities were demonstrated using plasmids carrying cloned DNA containing the E element or the RFB region (3,13,38), the observed activities were reported to be very weak compared to the activities in the chromosomal context (3). This situation resembles that observed for transcription of a reporter gene; transcription of a Pol I reporter on a plasmid was reported to be much weaker relative to transcription of the same reporter integrated into the chromosomal rDNA repeats (16).…”
Section: Vol 21 2001mentioning
confidence: 99%
“…In fact, based on their discovery of the FOB1 gene, which is required for both RFB activity and HOT1 activity, this model was proposed by Kobayashi and Horiuchi (14) as an alternative to the original explanation of HOT1 activity being solely a consequence of high-level transcription from the Pol I promoter. However, it was recently demonstrated that HOT1 activity can take place in the absence of replication fork blocking (38). Thus, the reason why both HOT1 and RFB activities require FOB1 has become a challenging question.…”
mentioning
confidence: 99%
“…In both bacteria, the numerous terminator (Ter) 1 sites are clustered in the terminal region of the chromosome and are arranged so as to control the location of replication fork fusion at the end of a round of replication (for a review see Ref. 10).…”
mentioning
confidence: 99%
“…They have roles in a variety of tasks, including the coordination of DNA replication and transcription at eukaryotic rDNA loci (1,2), regulation of mating-type switching in yeast by strand-specific imprinting during replication (3,4), and participation in the final stages of bacterial chromosome replication and partitioning (5).…”
mentioning
confidence: 99%